Simulation on dynamic load balancing of distributed parallel computing network system. Issue 3 (31st August 2021) - Wu, Huawei; Sun, Chuan; Li, Yicheng; Kuang, Yong
In order to improve the dynamic load balancing scheduling capability of distributed parallel computing network system and the throughput performance of network, a dynamic load balancing scheduling algorithm of distributed parallel computing network system is proposed. In this algorithm, a channel transmission model for task scheduling of distributed parallel computing network is constructed. The adaptive link equalisation method is adopted to perform balanced design of distributed parallel computing network transmission channel. The fractional interval interpolation method is adopted to construct the priority list decision function for dynamic load scheduling in balanced transmission channel. Based on the decision function, the balancing scheduling threshold of dynamic load of distributed computing network is determined to reach dynamic load balancing scheduling effect. The experimental results show that the method has strong anti-interference performance and the maximum amplitude of equilibrium state is 0.2. The data transmission throughput performance of distributed parallel computing network is improved.